“Phi Sa Oeng” Worship of the Kui at Ban La-o, Amphoe Nam Kliang, Changwat Sisaket - Srikhao, Pannawadee (Journal of Thai Studies, 2023)
Phi Sa Oeng are the family lineage ancestral spirits of the Kui at Ban La-o, Amphoe Namkliang, Changwat Sisaket. Their duty is to protect and take care of their descendants. If their descendants break the custom, the spirits can cause them illness. Annually, during the third and sixth month, villagers will arrange the ancestral spirit worship in order to fulf ill their vows, thank and worship the spirits. This worship helps transmit the belief in ancestral spirits. At the same time, the worship helps to transmit the customary law of the Kui at Ban La-o, teaches descendants and unites the relationship between the people in the community. In addition, the worship helps to build spirit for individuals and can respond to the spiritual needs of individuals and build the strength of the community. These are the reasons why the worship has been practiced for a long time until the present.